One-pot two-step catalytic synthesis of 6-amino-2-pyridone-3, 5-dicarbonitriles enabling anti-cancer bioactivity. Issue 37 (24th August 2022) - Nicely, Lynden G.; Vala, Ruturajsinh M.; Upadhyay, Dipti B.; Nogales, Joaquina; Chi, Celestine; Banerjee, Sourav; Patel, Hitendra M.
Abstract : The one-pot synthetic strategy of amino-pyridones with potent anti-cancer activity against breast, brain, liver, and lung cancer cells either alone or in combination with clinically relevant receptor tyrosine kinase and proteasome inhibitors. Abstract : We report a one-pot two-step synthesis of a bioactive 6-amino-2-pyridone-3, 5-dicarbonitrile derivative using natural product catalysts betaine and guanidine carbonate. Anti-cancer bioactivity was observed in specific molecules within the library of 16 derivatives. Out of the compounds, 5o had the most potent anti-cancer activity against glioblastoma cells and was selected for further study. Compound 5o showed anti-cancer properties against liver, breast, lung cancers as well as primary patient-derived glioblastoma cell lines. Furthermore, 5o in combination with specific clinically relevant small molecule inhibitors induced enhanced cytotoxicity in glioblastoma cells. Through our current work, we establish a promising 6-amino-2-pyridone-3, 5-dicarbonitrile based lead compound with anti-cancer activity either on its own or in combination with specific clinically relevant small molecule kinase and proteasome inhibitors.